PENGEMBANGAN POSDAYA BERBASIS MASJID GUNA TERWUJUDNYA KELUARGA SEJAHTERA MASJID DARUSSALAM DESA SRAGI KECAMATAN SONGGON KABUPATEN BANYUWANGI - Kholilur Rahman (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2018)
The implementation of the programme of study is based on the devotion of Introduction indicating that still lack creativity, motivation and spirit of entrepreneurship in Sragi village society and explores the potential of new business ideas. KKN Thematic Posdaya Sragi Subdistrict village mosque-based Songgon execute some programs which aim to regenerate spirit, motivation, creativity and knowledge in entrepreneurship. This program has been going well and was able to increase knowledge and understanding of the participants in managing natural resources is around their homes, particularly the rich natural areas of horticulture, increased motivation and militancy participants in managing entrepreneurship, so that possible participants can collaborate to form more productive entrepreneurial groups.